Comportamento mecânico de um solo siltoso da formação geológica Guabirotuba tratado com cal em diferentes tempos de cura - Baldovino, Jair de Jesús Arrieta (2018)
The use of lime as stabilizing material and improvement of fine soils such as clays and silts has been a widely used technique in geotechnical engineering. The Guabirotuba Formation is a geological formation of the Paraná basin, located in the city of Curitiba and Metropolitan Region, in Brazil; and extends over an area of approximately 900 km2. The soils of this Formation, in the majority, are classified like fine of the type smectites, being presented in different stains. In addition, the fine soils of the Formation can´t due to their physicalmechanical properties, be used many times for the construction of bases and sub-bases for paving, slope protection or for support of superficial foundations such as spread footings, due to the low support capacity, high expansibility when in contact with water and high erodibility when it does not have any type of surface protection. The treatment of this type with lime soil makes it compatible for these conditions of use.The present research aims to evaluate the mechanical behaviour of a silty soil of the Guabirotuba geological Formation treated with different amounts of lime (0%, 3%, 5%, 7% and 9%) at different curing times (15, 30, 60, 90 and 180 days) and compaction energies (standard, intermediate and modified). For this, the behaviour of unconfined compressive strength, or simple compression (qu), split tensile strength (qt) and direct shear strength parameters (internal friction angle Φ and cohesion C) was investigated. In addition, the influence of suction on the mechanical resistance of all soillime mixtures was also studied. The control parameters evaluated in the research were mainly: lime content (L), curing time (t), moisture content (ω), porosity (η), volumetric lime content (Lv) and the degree of saturation (S). The η/Lvratio was used to study the growth of qt and qu, and to determine the relation qt/qu at all cure times. It was observed that there were changes in soil compaction properties and at the Atterberg limits when the soil stabilized with lime, as well as a growth of the unconfined compressive strength (qu) and the split tensile strength (qt) with increasing lime content and curing time, and, on the other hand, an increase in the parameters of direct shear strength. The results show that there is a constant ratio of qt/qu =0,16 for all cure times. A general equation for predicting or estimating the resistance qu and qt of the soil-lime mixtures using the voids/lime ratio η/Lv was developed by normalizing the resistances at all cure times and it was verified that the equation may extend and to estimate the resistance of other soils of the Guabirotuba Formation with the ratio η/Lvadjusted to an exponent equal to 0,20.